Systematic video analysis of ACL tear patterns in Spanish professional female football players: neurocognitive errors as targets for prevention - Miralles-Iborra, A.; Buckthorpe, M.; Della Villa, F.; De los Ríos-Calonge, J.; Elvira, J. L. L.; Vera-Garcia, F. J.; Del Coso, J.; Moreno-Pérez, V. (Journal of Science and Medicine in Sport, 2025)
Objective This study aimed to analyse the mechanisms, injury patterns, biomechanics and neurocognitive factors of anterior cruciate ligament (ACL) tears in professional female Spanish football players during training and competitive matches.